Black Students Special Problems/Special Needs for Retention. - Jefferson Community Coll., Louisville, KY.; Jefferson Community Coll., Louisville, KY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Positive ideas were generated from two programs sponsored by the Jefferson Community College (Louisville, Kentucky) Black Affairs Advisory Committee and given during Black History Week. The first program consisted of a panel of seven black professionals from the Louisville community which discussed "What It Takes to Make It: A Message for Students." Nineteen suggestions for students were offered by this panel. The most important theme emerging from this program was that students should assume the major share of the responsibility for their own futures. The second program consisted of a faculty/staff development session which permitted the staff to share ways to encourage black student retention. Using a mini-group "think tank" process, the faculty exchanged ideas on how to handle two hypothetical classroom-based situations involving black students. Nineteen ideas were given by the staff for the first situation which focused on a disruptive, militant student. Fifteen ideas were generated for the second situation which involved a group of students who were motivated but had academic deficiencies. (EM)
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Problems; Black Students; Community Colleges; Guidelines; Learning Problems; Pamphlets; Positive Reinforcement; School Holding Power; Self Concept; Student Responsibility; Student Teacher Relationship; Teacher Responsibility; Two Year Colleges; Disruptive Behavior -- PF Project; Guides, Non-Classroom.